Repetitive DNA sequences near three human beta-type globin genes. - Coggins, L W (1980)
Five repetitive DNA sequences, of average length 259 bp, have been identified in the intergenic regions which flank three human beta-tupe globin genes. A pair of inverted repeat sequences, separated by 919 bp, was found 1.0 kb to the 5' side of the epsiln-globin gene. Each contains a homologous Alu I site. Another repetitive sequence, with the same orientation as the inverted repeat sequence closest to the epsilon-globin gene, lies about 2.2 kb to the 5' side of the delta-globin gene. A pair of inverted repeat sequences, with the same relative orientations as the other pair and separated by about 800 bp, was found about 1.5 kb to the 3' side of the beta-globin gene.